The Traditional Chinese Medicine Formula Jing Guan Fang for Preventing SARS-CoV-2 Infection: From Clinical Observation to Basic Research - Ping, Yueh-Hsin; Yeh, Hsin; Chu, Li-Wei; Lin, Zhi-Hu; Hsu, Yin-Chieh; Lin, Lie-Chwen; Hsu, Chung-Hua; Fu, Shu-Ling; Lin, Tung-Yi (Frontiers in Pharmacology, 2022)
COVID-19 is a global epidemic. Developing adjuvant therapies which could prevent the virus from binding to cells may impair viral infection. This study produces a traditional Chinese medicine formula, Jing Guan Fang (JGF), based on ancient medical texts, and examines the efficacy and the mechanism by which JGF prevents viral infections. JGF reduces COVID-19 like symptoms. Functional studies show that JGF inhibits the formation of syncytium and reduces the formation of viral plaque. JGF is not toxic in vitro and in vivo. Mechanistically, JGF induces lysosomal-dependent ACE2 degradation and suppresses mRNA and the protein levels of TMPRSS2 in human lung WI-38 and MRC-5 cells. Mice that inhale JGF exhibit reduced ACE2 and TMPRSS2 protein levels in lung tissues. Together, these findings suggest that JGF may improve the COVID-19 like symptoms and inhibit viral infection. Moreover, JGF may be applicable as an adjuvant preventive strategy against SARS-CoV-2 infection in addition to the use of vaccines.